Productive efficiency of organic vegetable grown in kitchen garden of Chitwan, Nepal - Dhakal, S. C. (Journal of Agriculture and Forestry University, 2020)
Kitchen gardening in general and organic vegetable production in particular are gaining popularity, and have been becoming indispensable component of Nepalese farming system. This concept could be promoted in order to reduce market dependency for vegetables; increase access to pesticide free products for home consumption, and for minimizing malnutrition and poverty. This research was done to estimate the cost, return, profitability and productive efficiency of organic vegetable grown in kitchen gardens of Chitwan using primary data, obtained from 123 randomly selected households. Samples were selected using simple random sampling techniques, and data were analyzed using Stata-12 for estimating descriptive statistics, Cobb- Douglas production function, allocative efficiency and frontier production function. Average size of holding for organic vegetable production was 0.65 kattha with gross margin of NRs. 9,312 per kattha and benefit cost ratio 2.19. Human labor, seed and organic manure significantly and positively contributed to the productivity of organic kitchen gardening, resulting return to scale value at 0.57. Majority of inputs, such as seed, organic manure, and irrigation were underutilized, and human labor was over utilized. Labour has been utilizing at technically efficient level in spite of its overutilization in allocative efficient measure. Almost all kitchen garden firms were operating at 90% efficiency and they require about NRs. 17,116 annual income per kattha for achieving this efficiency level. Organic vegetable production in kitchen garden system is profitable and there is scope to increase the expenditure on better seeds, organic manures, and irrigation for achieving the maximum productive efficiency by about 69, 61, and 496%, respectively. Policy support for promoting the distribution and adoption of vegetable seeds of improved varieties, composting, green manuring and increased use of irrigation seems fruitful to increase the productive efficiency of organic vegetable grown in kitchen garden of Chitwan district, Nepal.